Heterotypic Tumor Spheroids in Agitation-Based Cultures: A Scaffold-Free Cell Model That Sustains Long-Term Survival of Endothelial Cells - Franchi-Mendes, Teresa; Lopes, Nuno; Brito, Catarina (Frontiers in Bioengineering and Biotechnology, 2021)
Endothelial cells (ECs) are an important component of the tumor microenvironment, playing key roles in tumor development and progression, that span from angiogenesis to immune regulation and drug resistance. Heterotypic tumor spheroids are one of the most widely used in vitro tumor microenvironment models, presenting improved recapitulation of tumor microenvironments compared to 2D cultures, in a simple and low-cost setup. Heterotypic tumor spheroid models incorporating endothelial cells have been proposed but present multiple limitations, such as the short culture duration typically obtained, the use of animal-derived matrices, and poor reproducibility; the diversity of culture conditions employed hinders comparison between studies and standardization of relevant culture parameters. Herein, we developed long-term cultures of triple heterotypic spheroids composed of the HCC1954 tumor cell line, human fibroblasts, and ECs. We explored culture parameters potentially relevant for EC maintenance, such as tumor cell line, seeding cell number, cell ratio, and agitation vs static culture. In HCC1954-based spheroids, we observed maintenance of viable EC for up to 1 month of culture in agitation, with retention of the identity markers CD31 and von Willebrand factor. At the optimized tumor cell:fibroblast:EC ratio of 1:3:10, HCC1954-based spheroids had higher EC area/total spheroid area at one month of culture than the other cell ratios tested. EC maintenance was tumor cell line-dependent and in HC1954-based spheroids, it was also dependent on the presence of fibroblasts and agitation. Moreover, vascular endothelial growth factor (VEGF) supplementation was not required for maintenance of EC, as the factor was endogenously produced. ECs co-localized with fibroblasts, which accumulated preferentially in the core of the spheroids and secreted EC-relevant extracellular matrix proteins, such as collagen I and IV. This simple model setup does not rely on artificial or animal-derived scaffolds and can serve as a useful tool to explore the culture parameters influencing heterotypic spheroids, contributing to model standardization, as well as to explore molecular crosstalk of ECs within the tumor microenvironment, and potentially its effects on drug response.